PENGUKUR PARAMETER SEARCH ENGINE OPTIMIZATION (SEO) SECARA ON PAGE PADA TOKO ONLINE UNTUK MENINGKATKAN PENJUALAN - Maskur Maskur (Adbis: Jurnal Administrasi dan Bisnis, 2019)
The current search engine is not only for searching the pages of the website you want to visit but also as the main source of visitors on the internet. With the development of technology several ways that can be used to improve website ranking on search engines, one effective way by utilizing Search Engine Optimization (SEO) can help some websites to get SERP rankings (Search Engine Results Pages) on search engines, by a good SERP ranking will then be determined on the number of visitors on the website. An application is needed to calculate SEO applications on a web site, with the application of Online SEO measurement parameters can help business users of online stores to increase visitors and invite visitors who become buyers. In the Complete SEO Parameter Measurement Application on this page has 6 important parameters in SEO on the page provided, Title Tag, Title Tag, Meta Description, Content, Alt Tag and Keyword Density, with an explanation of each - each parameter where The accuracy of the application results in the calculation can be obtained Kappa value of 0.57..